Mechanisms of Low-Temperature Nitridation Technology on a TaN Thin Film Resistor for Temperature Sensor Applications - Chen, Huey-Ru (Nanoscale Res Lett, 2016)
In this letter, we propose a novel low-temperature nitridation technology on a tantalum nitride (TaN) thin film resistor (TFR) through supercritical carbon dioxide (SCCO(2)) treatment for temperature sensor applications. We also found that the sensitivity of temperature of the TaN TFR was improved about 10.2 %, which can be demonstrated from measurement of temperature coefficient of resistance (TCR). In order to understand the mechanism of SCCO(2) nitridation on the TaN TFR, the carrier conduction mechanism of the device was analyzed through current fitting. The current conduction mechanism of the TaN TFR changes from hopping to a Schottky emission after the low-temperature SCCO(2) nitridation treatment. A model of vacancy passivation in TaN grains with nitrogen and by SCCO(2) nitridation treatment is eventually proposed to increase the isolation ability in TaN TFR, which causes the transfer of current conduction mechanisms.